Ketogenic diet for the treatment of refractory epilepsy: a 10 year experience in children Avaliação da dieta cetogênica no tratamento da epilepsia refratária em crianças: 10 anos de experiência - Alessandra Freitas; José Albino da Paz; Erasmo Barbante Casella; Maria Joaquina Marques-Dias (Arquivos de Neuro-Psiquiatria)
Ketogenic diet (KD) is a high fat and low carbohydrate diet, which controls refractory epilepsy. We analyzed the KD effects on 54 children of the Children's Institute of the University of São Paulo. Efficacy, tolerability, and adverse effects were studied. Response to KD was effective (E) if seizure control was >75%, good (G) when 50-75%. When possible, we correlated the results with the epileptic syndrome and patient's age. By the second month on diet, 57.4% of the patients had E response and 31.4% G results. At the 6th month, 63.8% had E response and 25.5% G. At the 12th month, 71.8% had E and 25.6% G. At the 24th month, 62.1% had E and 37.9% G. Antiepileptic drugs have been reduced, and generalized epilepsy was the most sensitive. Age-related differences were not observed. Adverse effects were rarely observed. In conclusion, KD proved to be an effective treatment for refractory epilepsy. A dieta cetogênica (DC) tem alto teor de gordura e baixo de carboidratos e proteínas, sendo usada no tratamento da epilepsia refratária. Analisamos os efeitos da DC em 54 crianças do Instituto da Criança da Universidade de São Paulo. Eficácia, tolerabilidade e efeitos adversos foram estudados. A DC foi considerada eficaz (E) quando houve redução de crises >75% e boa (B) quando a redução foi entre 50-75%. Correlacionamos, quando possível, esses resultados com a síndrome epiléptica e com a idade dos pacientes. Observamos resultados (E) em 57,4%, 63,8%, 71,8% e 62,1% dos pacientes no 2º, 6º, 12º e 24º meses, respectivamente e (B) em 31,4%, 25,5%, 25,6% e 37,9%, respectivamente. Houve redução significativa das drogas antiepilépticas. A DC foi mais eficaz nas epilepsias generalizadas e não houve diferenças quanto a idade. Efeitos adversos foram raros. Em conclusão, a DC é um tratamento antiepiléptico eficaz em casos refratários.